Electronic cigarettes and their effects on human health - Majewski, Maciej; Chruścicka, Izabela; Buchta, Justyna; Egierska, Dominika; Burzyńska, Paulina; Pietruszka, Paulina; Perszke, Michał; Całkosiński, Aleksander (Journal of Education, Health and Sport, 2020)
In the last decade electronic cigarettes also known as e-cigarettes have gained popularity. These are devices designed to imitate regular cigarettes. They provide nicotine via inhalation without using tabacco. The introduction of alternative nicotine delivery devices to the consumer market has inspired a vivid debate on the harmfulness of these products. It is discussed whether they are regulated, safe and as harmless as it is claimed. The purpose of this article was to describe the chemical composition of the e-cigarettes and its influence on human’s health. The devices contain many various groups of potentially toxic and carcinogenic compounts: carbonyls, volatile organic compounts and nitrosamines. The researchs has shown that e-cigarettes contain significantly lower concentration of those substances than the traditional cigarettes. On the other hand, it should be remembered that scientists still do not know potential long term pathologies caused by the liquids.